Vinde a mim os pequeninos: uma contribuição teológica e psicológica ao estudo da infância - Quilião, Maria Helena (2013)
This research has used the James Loder's literary work and his theological proposal about human progress. In the moment there is no translation to portuguese, so this is the reason to propagate these conception for whole population. This essay aims to introduce study of childhood, accentuating psychological and theological's aspects. The first chapter was analyzed psychological contribution and its progress, which was used Sigmund Freud's Psychoanalytic Theory and Erik Erikson's Psychosocial Theory in this research. The second chapter the psychological aspect was researched presenting rich contribution from the theologian James Loder. Loder propose in his theory The Logic of the Spirit a theological definition about the capacity of the human to create and build smart solution to save himself from the chaos. Scientific and technological progress are the search result from human to connect with a superior reality, restless finite and seclusion. Loder with his proposal connect knowledge already accepted by psychology with theology. Another very important point in the Loder's theory is about relationality, there is an undeniable relation between human spirit and Divine Spirit, between man and God. In the third chapter was gathered research that can be used to study or lectures for lay public. The objective is support the knowledge that there is logic in the human spirit, logic which search save the human being from his chaos, from egocentrism and his self destruction, and give him a balanced existence, healthy and successful relationship with God.